2021
DOI: 10.1177/09544089211065534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 nanoparticles on microstructure and mechanical properties of friction stir-welded dissimilar aluminum alloys AA7075-T6 and AA6061-T6

Abstract: In this research, a defect-free dissimilar weld joint of AA7075-T6 and AA6061-T6 reinforced with Al2O3 nanoparticles was fabricated via friction stir welding (FSW). The influence of tool rotational speed (700, 900 and 1100 rpm), traverse speed (40, 50 and 60 mm/min) with varying volume fractions of Al2O3 nanoparticles (4%, 7% and 10%) on microstructural evolution and mechanical properties were investigated. The augmentation of various mechanical properties is based on the homogeneity of particle dispersion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…They found that it was due to the flow of the material from the top to bottom (i.e. warmer to colder) beneath the NZ or due to insufficient heat generation and partial recrystallization occurring in the nugget zone during the FSW process [94][95][96][97][98].…”
Section: Onion Ring Formation In the Nzmentioning
confidence: 99%
“…They found that it was due to the flow of the material from the top to bottom (i.e. warmer to colder) beneath the NZ or due to insufficient heat generation and partial recrystallization occurring in the nugget zone during the FSW process [94][95][96][97][98].…”
Section: Onion Ring Formation In the Nzmentioning
confidence: 99%
“…5b. This demonstrates that one FSW pass was not producing su cient strain to prevent clustering of SiCp [30]. The clustering of SiCp was found absent as the FSW passes enhanced from one to two, but the dispersion pattern of SiCp was observed as non-uniform in the two-passes FSWed reinforced joint, as cited in Fig.…”
Section: Microstructural Characterizationmentioning
confidence: 68%
“…53 Smaller grain size exhibits higher hardness as per Hall–Petch relationship. 5456
Figure 11.Micro-hardness profile of composite Joints, (a) at 700rpm, (b) at 900 rpm, (c) 1100 rpm.
…”
Section: Resultsmentioning
confidence: 99%
“…53 Smaller grain size exhibits higher hardness as per Hall-Petch relationship. [54][55][56] The micro-hardness of the composite joints embedded with reinforcement particles also enhanced due to the presence of hard Al 2 O 3 particles. Therefore, the strengthening impact of Al 2 O 3 mp in specimen no-12 was observed higher in comparison with other specimens, due to the increased volume fraction of hard Al 2 O 3 mp, higher grain refinement, and enhanced material mixing rule.…”
Section: Influence Of Al 2 O 3 Mp On Tensile Strengthmentioning
confidence: 99%